Gender differences in delinquency at 21 years following childhood maltreatment: A birth cohort study. (1st February 2017) - Abajobir, Amanuel Alemu; Kisely, Steve; Williams, Gail; Strathearn, Lane; Clavarino, Alexandra; Najman, Jake Moses
Abstract: Childhood maltreatment and youth delinquency are major public health problems. The present study examines the association between exposure to agency substantiated childhood maltreatment from 0 to 14 years of age and delinquency at 21 years in males and females separately. The study uses data from the Mater Hospital-University of Queensland Study of Pregnancy, an Australian pre-birth longitudinal cohort of mothers and their children. Pregnant women were recruited consecutively at their first antenatal clinic visit at Brisbane's Mater Hospital from 1981 to 1983. We linked substantiated cases of childhood maltreatment, reported to the appropriate child protection services between birth and 14 years of age, to the 21-year survey follow-up. The study sample comprises 1810 males and 2008 females, who had complete data on delinquency at the 21-year follow-up. The odds of delinquency at the 21-year follow-up were 4–6 times higher for maltreated children in the unadjusted models. In the adjusted models, physical abuse, emotional abuse and neglect, as well as emotional abuse with or without neglect were associated with over 3 times a greater risk of delinquency in males. More frequent maltreatment was associated with double the risk of later delinquency in males. However, none of the maltreatment subtypes, nor was the frequency of maltreatment substantiations associated with an increased risk of delinquency in females. Exposure to any childhood maltreatment increased the likelihood of delinquency for males but there was no difference for females. Childhood maltreatment is associated with an increased risk of later delinquency for young adult males, but not females. Highlights: Childhood maltreatment is independently associated with an increased risk of youth delinquency in males but not in females. A higher frequency of maltreatment substantiations predicted later delinquency in males but not in females. These associations are above and beyond individual, familial, and environmental confounding factors.